Exfoliative Cytological Changes in Peritoneal Fluid from Patients on Peritoneal Dialysis - Kattab, Yarub I.; Al-Qazzaz, Mutaz A.; Mousa, Liqaa R. (AL-Kindy College Medical Journal, 2008)
Background: Ambulatory peritoneal dialysisintroduced by Popvich et al (13) in 1978 , consists of afour to five hours lavage of peritoneal cavity with 2000ml of glucose solution .It remains a useful method fortreating patients with end stage renal failure till renaltransplantation becomes possible.Objectives: The aim of the study is to evaluate thevalue of cytological changes of mesothelial cells indialysate patients.Methods: Within one year period, 32 cytologicalperitoneal fluid samples were collected from patientswith end stage renal failure regardless of the underlyingcauses, admitted to the dialyzing unit in KadimyaTeaching Hospital. Smears were prepared and fixed in95 % ethyl alcohol and then stained with H & E stain tobe interpreted by the same pathologist.Results: Thirty two samples of peritoneal fluid wereobtained from patients in peritoneal dialysis with amean age of 54.8 years and male to female ratio ofabout 1.9: 1.Twenty two had short term dialysis were compared with10 patients with long term dialysis.Gross examination of the samples revealed clear yellowfluid. Macroscopical examination showed no evidenceof inflammatory cells with increased exfoliation,cellularity and three dimensional mesothelial cellularclustering pattern with increased nuclear size. Nostatistical significances were found in the changes seenin cytological smears between both groups butremarkable nuclear changes were shown in both ofthem.Conclusion: This study demonstrated that peritonealdialysis of any duration can induce significant atypicalchanges in mesothelial cells. The pathologist needs tobe aware of these changes and to include peritonealdialysis in the list of other benign conditions that causereactive mesothelial atypia